Classification of the Signatures for Doppler Radar from the Standpoint of Active Perception Theory; Key Engineering Materials; Vol. 685 : High Technology: Research and Applications 2015 (HTRA 2015) - Gai V. E. (Numerical Simulation of Physical and Chemical Processes, 2016)
Title screen